Pengembangan LKPD Tematik Berbasis Project Based Learning Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Raudatul Muaiyana; Ridwan Ridwan; Muhammad Ali (Journal on Education, 2023)
Development of Student Worksheets on thematic learning through the application of project based learning (PjBL) for elementary school students at SD Negeri 1 Perampuan. Based on the problems that occur in the classroom in the form of low student learning outcomes, lack of active involvement of students in the learning process and the absence of student worksheets developed by the teacher. So the learning resources used are only theme books published by the ministry. These teaching materials have not been modified according to student needs, so student learning outcomes are low and they are less motivated to participate in the learning process. The method used in this research is Borg and Gall type R&D by applying 8 research steps due to limited research time. Based on the results of the research conducted, thematic student worksheets through the application of project based learning are valid and suitable for testing. This is based on the validation results of content, design and language experts. Content validation obtained a score of 80% in the appropriate category, design validation obtained a score of 87.7% in the very valid category and language validation obtained a score of 77.5% in the valid category. Meanwhile, learning tools in the form of a syllabus and learning implementation plan obtained validation scores of 90.4 (syllabus) and 90.8 (RPP). Based on small-scale trials, an average score of 90.4% was obtained in the valid category. The results of the normality test analysis obtained scores on the experimental pretest 0.200 > 0.05 (valid), experimental posttest 0.094 > 0.05 (valid), control pretest 0.200 > 0.05 (valid), control posttest 0.192 > 0.05 (valid). The data homogeneity test results obtained were 0.247 > 0.05 (homogeneous). The results of the independent sample t test obtained a sig (2-tailed) score of 0.000 < 0.05 (there is an influence) and the ngain score for the experimental class was obtained at 72.1214 (quite effective) and the ngain score for the control class was 7.1882 (less effective). From the research data, it can be concluded that the use of thematic student worksheets through the application of project based learning is quite effective in improving student learning outcomes.